A Kindergarten Center - Brenda H. Gracey; Robert N. Kratz; Audrey G. Sprenger (Journal of Research in Rural Education, 1983)
This paper describes an approach to centralization of classes in a school system with numerous small school buildings. The reasons for development of a kindergarten center are described as are the positive and negative aspects of the kindergarten center.